Customer Satisfaction on Public Transportation in Penang, Malaysia - Sobanah Dhevi, Tharmalingam; Sai, Mei Ling; Vikniswari, Vija-Kumaran; Kalai Vani, Kalimuthu; Suresh, Nodeson (INTI International University, 2022)
This paper reports the customers’ satisfaction about public transportation service in Penang, Malaysia. In this respect, some of the factors namely reliability, accessibility, safety and security are used to measure the customers’ satisfaction on bus service Rapid Penang, Malaysia. A survey was conducted where questionnaires were distributed to 500 bus passengers. The results of the study indicates that reliability, accessibility, safety and security of bus service are positively significant to customer satisfaction. The contribution of the study creates better understanding of the service provider the factors that able increase customers’ satisfaction and base on the knowledge they able to improve their services and gain the customers’ trust.